Operational focus: Sourcing in the Process Industries Fashionable Again? - Hartmann, Evi; Salehi, F.; Vallerien, S. (Chemical Market Reporter, 2003)
The importance of procurement during the recent recessive times is discussed. A tailor made sourcing strategy can significantly increase the profitability, market share and technological innovation of process companies. Companies are pursuing strategic sourcing applications in line with the sourcing categories and are readily adapting to e-procurement tools.
WiSo-Import:2015-03-26:1246
Keywords: Innovation